2020
DOI: 10.2147/jpr.s249493
|View full text |Cite
|
Sign up to set email alerts
|

<p>Risk Factors Associated with Postoperative Discomfort After Ambulatory Strabismus Surgery Under General Anesthesia</p>

Abstract: The aim of this study was to evaluate postoperative discomfort in patients undergoing ambulatory strabismus under general anesthesia, and to identify risk factors associated with the discomfort. Patients and Methods: A cross-sectional study was conducted among 210 consecutive patients undergoing ambulatory strabismus under general anesthesia. Postoperative discomfort including nausea, vomiting, dizziness, and headache was recorded and quantified. Univariable and multivariable logistic regression were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Li et al [30] showed that the duration of surgery was an independent risk factor for PONV, with a cut-off point of 29.5 minutes, sensitivity of 1.00, and speci city of 0.64. In addition, Huang et al [4] reported that female sex, inferior rectus surgery, and inferior oblique surgery were independent risk factors for adult postoperative vomiting. Similar to previous studies, we found that a history of PONV or motion sickness and IOAT were risk factors for PONV in children who underwent strabismus surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [30] showed that the duration of surgery was an independent risk factor for PONV, with a cut-off point of 29.5 minutes, sensitivity of 1.00, and speci city of 0.64. In addition, Huang et al [4] reported that female sex, inferior rectus surgery, and inferior oblique surgery were independent risk factors for adult postoperative vomiting. Similar to previous studies, we found that a history of PONV or motion sickness and IOAT were risk factors for PONV in children who underwent strabismus surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ye' study [2] on postoperative pain and discomfort in patients who underwent oculoplastic surgery under general anesthesia showed that anxiety was a risk factor for both postoperative pain and discomfort, while smoking history and prior surgery on the operative eye may be associated with postoperative pain. Similarly, Huang et al [4] reported that 94.76% of adult patients experienced mild discomfort after ambulatory strabismus surgery under general anesthesia; independent predictors of postoperative discomfort included female sex, inferior rectus surgery, mild anxiety, and inferior oblique surgery.…”
Section: Introductionmentioning
confidence: 89%
“…This is primarily attributed to the disparity in hormone levels between men and women, particularly the elevated levels of serum sex hormones, progesterone, and estrogen in female patients. Hormonal uctuations post-surgery are substantial, leading to symptoms such as nausea, vomiting, and irritability in some female patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…The association was significant for a value of p<0.05. [6,8,[10][11][12]. In various studies, complications of prematurity such as sepsis, intraventricular hemorrhage, and necrotizing enterocolitis have been suggested to be responsible for retinopathy of prematurity (ROP) and cortical visual dysfunction [3].…”
Section: Methodsmentioning
confidence: 99%